Sistem SOLART Berbasis ESP32 untuk Kendali Otomatis Lampu dan Tirai Berdasarkan Intensitas Cahaya - Muhammad Ihsan Wafiudin; Achmad Solichan; Aris Kiswanto (Jurnal Teknik Informatika dan Teknologi Informasi, 2026)
Residential lighting and curtains are commonly controlled independently, limiting daylight utilization and increasing reliance on electric lighting. This study developed SOLART, an ESP32-based local embedded system that integrates automatic lamp switching and curtain actuation using ambient light intensity as the control variable. The prototype employed an LDR-LM393 module, a one-channel relay for a 5 W AC lamp, and a BTS7960 motor driver connected to a DC motor. A rule-based threshold of 100 lx was implemented in Arduino IDE with a two-second sampling interval. Functional and electrical tests were conducted on the controller, sensor, relay, motor driver, motor, and lamp. At 70 lx, the system switched the lamp on and closed the curtain; at 220 lx, it switched the lamp off and opened the curtain. The sensor estimates differed from lux-meter readings by 1.43% and 0.45%, respectively. Relay and motor measurements generally showed deviations below 6%. A 19.39% deviation in the BTS7960 control-voltage reading was attributed to the limitation of measuring a switching or PWM signal with a handheld multimeter and therefore requires oscilloscope verification. The results demonstrate functionally consistent dual-actuator local control without internet dependence, although broader calibration, response-time measurement, and long-term energy testing remain necessary.